A Study on Enhancing Efficiency of a Filter for Arsenic Removal - Jannat, Kashmary; Khaleque, Tania S (GANIT: Journal of Bangladesh Mathematical Society, 2022)
Arsenic (As), a naturally occurring element found in rocks and in the Earth’s crust, is one of the most dangerous things that can get into drinking water. A unique system for filtering arsenic has been developed that makes use of naturally available laterite soil. To scale this technology and realize its full potential, a deep understanding of the relationship between filter life and operating regime (inlet concentration of arsenic, filter size, and laterite material) is required. We aim to study a mathematical model that presents relationship between the concentration (c) and adsorption (Γ) with dimensionless time. Based on Langmuir kinetics, the model integrates intra-particle mass transport of the contaminant within the filter medium. The model predicts the dependency of the filter adsorption rate and outlet concentration on several dimensionless parameters. Filter efficiency for both treated laterite and raw laterite are also studied here. GANIT J. Bangladesh Math. Soc. 42.2 (2022) 24- 38